Protein labelling and albumin binding characteristics of the near-IR Cy7 fluorophore, QuatCy. Issue 30 (18th July 2019) - Thavornpradit, Sopida; Usama, Syed Muhammad; Lin, Chen-Ming; Burgess, Kevin
Abstract : "QuatCy" selectively labels Cys side-chains, and proteins with exposed Cys residues over albumin. Abstract : Free cysteine residues react with QuatCy 1, by simply mixing the protein and dye in aqueous buffer at 37 °C. Another dye, MHI-148, can be used for a similar labelling protocol, but QuatCy reacts faster with all proteins studied, except albumin; it emerges here that this is because MHI-148 instantly forms of a non-covalent complex with albumin, but QuatCy does not. Labelling with QuatCy has advantages insofar as it is over five times brighter, and much more photostable, than MHI-148, and combination labelling with this dye pair will allow multiplexing in the near-IR region.